Mutational Analysis to Define the Functional Role of the Third Intracellular Loop of D1-Class Dopaminergic Receptors - Albaker, Awatif (Université d'Ottawa / University of Ottawa, 2016)
The third intracellular loop (IL3) and cytoplasmic tail (CT), which are the most divergent regions between human D1-class dopaminergic receptors (hD1R and hD5R), have been implicated in modulating their subtype-specific functional phenotypes. The importance of the IL3 for Guanine nucleotide-binding protein (G-protein) coupling and specificity has long been acknowledged in the G-protein-coupled receptor (GPCR) field. However, the exact role the central region of the IL3, notably the N- and C-terminal moieties, plays in GPCR receptor functionality remains unclear. Studies in our laboratory indicated that the IL3/N-terminal moiety of hD1-class receptors appears to be critical for facilitating agonist-independent and dependent activation of hD1R and hD5R. Furthermore, the IL3/C-terminal portion of hD1-class receptors constrains the receptor in the inactive state and reduces receptor affinity for agonists and G-protein coupling. I put forward the following hypothesis: 1. The functional properties of hD1-class receptors are regulated via a molecular micro-switch present within the IL3 central region modulating the functional properties of the receptor distinctly, 2. The functional differences between D1R and D5R require structural elements from both N- and C-terminal halves of the IL3 central region, and 3. The molecular interplay between the N- and C-terminal halves of the IL3 central region is dependent on the amino acid chain length and content. Herein, I have employed site-directed mutagenesis, and alanine replacement approaches to analyze comprehensively the structural determinants within the N- and C-terminal moieties of the IL3 central region that regulate ligand binding and G-protein coupling properties of hD1-class receptors. Moreover, my Ph.D. research aimed to pinpoint whether the IL3 length and/or structural motif(s) regulate ligand binding and activation properties of hD1R and hD5R. The results of my study highlight the importance of structural elements from both the proximal and distal segments of the IL3/central region of hD1-class receptors for the ligand binding and receptor activation status. Additionally, my results underline the significance of preserving the length of the IL3 regardless of the amino acid content. This study also shows the pivotal role played by a phenylalanine residue, F2646.27, in the signaling properties of hD1R. Notably, mutating F2646.27 leads to a mutant hD1R with characteristics resembling those of constitutively active mutant GPCRs. Unraveling the amino acid/amino acids constraining the receptor in the inactive state will perhaps provide an attractive target for drug design. Future work aims at developing drugs that particularly bind to the intracellular face of hD1R and improving selectivity towards hD1R may prove useful in limiting the side effects associated with the conventional therapy of brain disorders such as in the case of L-DOPA induced dyskinesia (LID) seen in individuals suffering from Parkinson’s disease.
Keywords: GPCRs; D1R; D5R; IL3; Dopamine